Whole brain radiotherapy plus concurrent chemotherapy in non-small cell lung cancer patients with brain metastases: a meta-analysis. - Hong Qin (PLoS ONE, 2014)
The aim of the present meta-analysis is to evaluate the response rate, median survival time (MST) and toxicity in patients with brain metastases (BM) originating from non-small cell lung cancer (NSCLC) and who were treated using either whole brain radiotherapy (WBRT) plus concurrent chemotherapy or WBRT alone.PubMed, EMBASE, Web of Science, The Cochrane Library, clinical trials and current controlled trials were searched to identify any relevant publications. After screening the literature and undertaking quality assessment and data extraction, the meta-analysis was performed using Stata11.0 software.In total, six randomized controlled trials (RCT) involving 910 participants were included in the meta-analysis. The results of the analysis indicate that WBRT plus concurrent chemotherapy was more effective at improving response rate (RR = 2.06, 95% CI [1.13, 3.77]; P = 0.019) than WBRT alone. However, WBRT plus concurrent chemotherapy did not improve median survival time (MST) (HR = 1.09, 95%CI [0.94, 1.26]; P = 0.233) or time of neurological progression (CNS-TTP) (HR = 0.93, 95%CI [0.75, 1.16]; P = 0.543), and increased adverse events (Grade≥3) (RR = 2.59, 95% CI [1.88, 3.58]; P = 0.000). There were no significant differences in Grade 3-5 neurological or hematological toxicity between two patient groups (RR = 1.08, 95%CI [0.23, 5.1]; P = 0.92).The combination of chemotherapy plus WBRT in patients with BM originating from NSCLC may increase treatment response rates of brain metastases with limited toxicity. Although the therapy schedule did not prolong MST or CNS-TTP, further assessment is warranted.